2018
DOI: 10.2135/cropsci2017.04.0264
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Oat Accessions for Fusarium Head Blight Resistance Using Spawn‐Inoculated Field Experiments

Abstract: Use of resistant cultivars is one of the most important measures to reduce the risk of Fusarium head blight (FHB, caused by various Fusarium spp.) and mycotoxins in cereals. Research on resistance to FHB has mainly focused on wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) and is very limited in oat (Avena sativa L.). In Norway, routine testing of cultivars and breeding lines has been performed in spawn‐inoculated field experiments with Fusarium graminearum Schwabe as part of a concerted research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 27 publications
(49 reference statements)
10
44
2
1
Order By: Relevance
“…In our study, VSS was reliably evaluated in all years only 14 days after inoculation, and we found it difficult to assess these symptoms in oats in comparison with wheat. This finding is in agreement with other studies on oats resistance (Tekauz et al, 2008;Gagkaeva et al, 2011), because at later developmental stages it becomes difficult to differentiate between natural senescence and FHB symptoms (Tekle et al, 2018). Severe symptoms attributed to Fusarium infections in oats are generally rare, and these are mainly observed in Northern Europe (Tekle et al, 2013).…”
Section: Correlation Coefficients Between Don and T-2supporting
confidence: 91%
See 2 more Smart Citations
“…In our study, VSS was reliably evaluated in all years only 14 days after inoculation, and we found it difficult to assess these symptoms in oats in comparison with wheat. This finding is in agreement with other studies on oats resistance (Tekauz et al, 2008;Gagkaeva et al, 2011), because at later developmental stages it becomes difficult to differentiate between natural senescence and FHB symptoms (Tekle et al, 2018). Severe symptoms attributed to Fusarium infections in oats are generally rare, and these are mainly observed in Northern Europe (Tekle et al, 2013).…”
Section: Correlation Coefficients Between Don and T-2supporting
confidence: 91%
“…In the present study, we found no significant correlation between plant Table 3). The effect of passive resistance mechanisms apparently depends on the genotypes tested and also on inoculum pressure and environmental conditions that determine disease development on plants (Tekle et al, 2018).…”
Section: Correlation Coefficients Between Don and T-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Spawn-inoculated field experiments were carried out in 2015 at the Vollebekk research farm, Norwegian University of Life Sciences (59 • 39 N, 10 • 39 E), as previously described in [7]. The RIL from each cross were tested in two separate experiments using an alpha lattice experimental design with two replications sown early May.…”
Section: Spawn-inoculated Field Experimentsmentioning
confidence: 99%
“…To overcome this, both the etiology of disease [4] and the resistance [5,6] have been studied. Breeding has reduced mycotoxin levels by 40% [7], but the mechanisms are not well understood.…”
Section: Introductionmentioning
confidence: 99%